Two new Andean species of Alychna Grishin, 2019 (Hesperiidae, Hesperiinae, Hesperiini, Moncina) from Bolivia and Peru - de Medeiros, Adalberto Dantas; Dolibaina, Diego Rodrigo; Mielke, Olaf Hermann Hendrik; Casagrande, Mirna Martins (Zootaxa, 2020)
Two new species of Alychna Grishin, 2019, Alychna chulumani Medeiros, Dolibaina & O. Mielke sp. nov. from Bolivia (La Paz, Chulumani) and Alychna argenteus Medeiros, Dolibaina & Casagrande sp. nov. from Peru (Huánuco, Carpish) are described. Illustrations of the wing pattern, forewing stigma and male genitalia of the two species are provided.